2021
DOI: 10.3390/ijms22105105
|View full text |Cite
|
Sign up to set email alerts
|

A Heterotypic Tridimensional Model to Study the Interaction of Macrophages and Glioblastoma In Vitro

Abstract: Background: Glioblastoma multiforme (GBM) is the most frequent and aggressive primary brain tumor, and macrophages account for 30–40% of its composition. Most of these macrophages derive from bone marrow monocytes playing a crucial role in tumor progression. Unraveling the mechanisms of macrophages-GBM crosstalk in an appropriate model will contribute to the development of specific and more successful therapies. We investigated the interaction of U87MG human GBM cells with primary human CD14+ monocytes or the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Some cell lines spontaneously aggregate when adherence to the substrate is restricted by using specific nonadherent culture plates. This easy, inexpensive technique is particularly suitable for the generation of spheroids and has already been used with different cancer cell lines, including breast (4T1), , intestinal (HCT116), bladder (MGH-U3/T24), ovarian (OVCAR3), pancreatic (HPAC), and brain (U87MG) cell lines. Different types of culture plates can be used, such as NUNCLON SPHERA 96-well U bottom plates, ultralow attachment 96-well plates, , ultralow attachment 6-well plates, or NanoCulture 96-well plates with a microsquare pattern .…”
Section: What Kind Of Materials? (Matrix Equipment Cancer Cell)mentioning
confidence: 99%
See 2 more Smart Citations
“…Some cell lines spontaneously aggregate when adherence to the substrate is restricted by using specific nonadherent culture plates. This easy, inexpensive technique is particularly suitable for the generation of spheroids and has already been used with different cancer cell lines, including breast (4T1), , intestinal (HCT116), bladder (MGH-U3/T24), ovarian (OVCAR3), pancreatic (HPAC), and brain (U87MG) cell lines. Different types of culture plates can be used, such as NUNCLON SPHERA 96-well U bottom plates, ultralow attachment 96-well plates, , ultralow attachment 6-well plates, or NanoCulture 96-well plates with a microsquare pattern .…”
Section: What Kind Of Materials? (Matrix Equipment Cancer Cell)mentioning
confidence: 99%
“…All of these plates have a specific coating to prevent cell adhesion and allow the formation of homogeneous spheroids. Hanging drop plates can also be used, , in which case 20 μL drops are deposited on the lid. Another technique is to use conventional plates (96 U-well and 6-well), subsequently treated with an agent, such as poly-2-hydroxyethyl methacrylate (poly-Hema), to prevent cell adhesion and allow good spheroid formation .…”
Section: What Kind Of Materials? (Matrix Equipment Cancer Cell)mentioning
confidence: 99%
See 1 more Smart Citation
“…Utilizing a similar method, another study was able to deliver monocytes that were loaded with conjugated polymer nanoparticles into GB cells and that allowed for the expansion and improvement of photodynamic therapy for GB [ 43 ]. Additionally, another experiment by Gattas and colleagues, [ 44 ] used primary monocytes that were cultured in the presence of U87MG-conditioned media, and co-cultured with GB spheroids. They found that monocytes differentiated and acquired clear M2 phenotypes, while also inducing alterations in the cell cultures.…”
Section: Cell Therapy For Glioblastomamentioning
confidence: 99%
“…They found that monocytes differentiated and acquired clear M2 phenotypes, while also inducing alterations in the cell cultures. The fact that these monocytes upregulated CD206, CD163 and MERTK surface markers on the CD11b and CD14 populations made them strong inducers of anti-inflammatory macrophages [ 44 ]. These three studies can be referenced together to show the range of ways that immune cells can be used to provide care to those with life-devastating tumors.…”
Section: Cell Therapy For Glioblastomamentioning
confidence: 99%